Signaling via a CD28/CD40 chimeric costimulatory antigen receptor (CoStAR™), targeting folate receptor alpha, enhances T cell activity and augments tumor reactivity of tumor infiltrating lymphocytes - Kalaitsidou, Milena; Moon, Owen R.; Sykorova, Martina; Bao, Leyuan; Qu, Yun; Sukumaran, Sujita; Valentine, Michael; Zhou, Xingliang; Pandey, Veethika; Foos, Kay; Medvedev, Sergey; Powell Jr, Daniel J.; et al. (Frontiers in Immunology, 2023)
Transfer of autologous tumor infiltrating lymphocytes (TIL) to patients with refractory melanoma has shown clinical efficacy in a number of trials. However, extending the clinical benefit to patients with other cancers poses a challenge. Inefficient costimulation in the tumor microenvironment can lead to T cell anergy and exhaustion resulting in poor antitumor activity. Here, we describe a chimeric costimulatory antigen receptor (CoStAR) comprised of FRα-specific scFv linked to CD28 and CD40 intracellular signaling domains. CoStAR signaling alone does not activate T cells, while the combination of TCR and CoStAR signaling enhances T cell activity resulting in less differentiated T cells, and augmentation of T cell effector functions, including cytokine secretion and cytotoxicity. CoStAR activity resulted in superior T cell proliferation, even in the absence of exogenous IL-2. Using an in vivo transplantable tumor model, CoStAR was shown to improve T cell survival after transfer, enhanced control of tumor growth, and improved host survival. CoStAR could be reliably engineered into TIL from multiple tumor indications and augmented TIL activity against autologous tumor targets both in vitro and in vivo. CoStAR thus represents a general approach to improving TIL therapy with synthetic costimulation.